Effects of Ethrel on Organogenesis of Protocorm-like bodies in Dendrobium kingianum In vitro (Plant Tissue Culture and Biotechnology, 2018)
Abstract not availablePlant Tissue Cult. & Biotech. 28(1): 141-146, 2018 (June)